Effect of different chain lengths of monoglyceride on the O/W interfacial properties with high-melting and low-melting crystals in low-fat aerated emulsion - Han, Wanjun; Chai, Xiuhang; Zaaboul, Farah; Sun, Yanwen; Tan, Chin-Ping; Liu, Yuanfa (Elsevier, 2023)
The effect of different types of monoglycerides, including monopalmitin, capryl monoglyceride (GMB), and succinylated monoglyceride (GMSA) in combination with palm kernel stearin (PKS) and beeswax (BW), on the formation, crystal network structure, and partial coalescence properties of aerated emulsions (20 % w/w fat) was investigated. The stability of BW and PKS crystals with a 1 % concentration of GMSA and GMB, respectively, in the oil phase was lower than the other crystals. BW-GMSA and PKS-GMB crystals exhibited a lower crystallization rate, higher contact angles and no significant peak shift in the small-angle X-ray scattering results. The BW-GMSA and PKS-GMB emulsions had a lower nucleation rate in the bulk and a higher nucleation rate at the interface, resulting in a higher fraction of crystals adsorbed at the oil/water interface. This reduced the number of interfacial proteins and led to a high degree of partial coalescence and the formation of stable aerated networks.